MULTIMEDIA-BASED INTERACTIVE LEARNING MEDIA FOR DEAF AND MENTALLY DISABLED ELEMENTARY STUDENTS ON SLBN 1 LENGAYANG - Dinda Djesmedi; Mellya Rindhani Aditia; Fitri Firdalius; Rasmita (Jurnal Teknik Informatika (Jutif), 2022)
The ability to remember and understand is quite difficult in the learning activities of mentally retarded and deaf students at SLBN 1 Lengayang. This study aims to examine the use of interactive media to assist the learning activities of deaf and mentally retarded students in improving understanding and memory. The data collection method used is the interview method and literature study. While the method used for the design and manufacture of the author's application uses UML and Storyboard which is implemented with Adobe Flash CS6. The result of the design is the Learning Application to Know Our Body Parts and a companion book to Know the Parts of the Body. Data analysis shows that using interactive learning media for deaf and mentally retarded children can improve memory and understanding with a more interesting and interactive learning process. The use of interactive multimedia in the form of applications and companion books is a new learning medium in the learning process that provides a different learning experience for deaf and mentally retarded students.